TH1.2: Gender in Livestock Agripreneurship: Implications for Inclusive Dairy Value Chain Development in Tanzania - Omondi, Immaculate A.; Omore, Amos O.; Galiè, Alessandra; Teufel, Nils; Baltenweck, Isabelle (International Livestock Research Institute, 2022)
Sub-Saharan Africa has the highest rate of entrepreneurship in the world with more women in entrepreneurship. However, women profit about 30 percent less compared to men and are usually less present in profitable non-producer livestock value chain nodes. To inform policy and strategic intervention for inclusive dairy value chain development, it is imperative to understand how men and women and youths thrive as agripreneurs. To assess both economic and non-economic outcomes (mainly empowerment) of men, women and youth's involvement in dairy-related businesses, we use data collected from 92 dairy agripreneurs from Kilimanjaro and Tanga regions of Tanzania. We use partial least-squares – structural equilibrium model (PLS-SEM), a non-parametric approach that places fewer limitations on sample size and data distribution, to build hypotheses around cause–effect relationships between the outcomes. Though no significant difference was observed in terms of profitability, our results, revealed that women and comparatively lowly educated agripreneurs scored significantly lower in business sustainability. Our PLS-SEM results revealed significant relationship between indicators that define business structure and empowerment. Moreover, men and women differed in terms of the indicators that significantly defined empowerment in its relationship with indicators of structure and business performance. For instance, ‘work-balance' was significant for both men and women, but ‘autonomy in income' was only significant for men, implying the need for varying approaches for supporting the empowerment of men and women agripreneurs. The evidence of the relative importance and interdependence of the indicators serves to inform further causal-link research and initial recommendations for designing inclusive interventions.